2015
DOI: 10.5539/ijbm.v10n10p158
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Website Performance and Online Retailer Status on Consumer Purchase Intention: A Mediator Role of Buyer Perception

Abstract: Purpose: The purpose of this research is to examine the effect of website performance and online seller status on consumer purchase intention. This study also aims to assess the mediation effect of buyer perception on the relationship between website performance and consumer purchase intention in the context of Internet shopping.Design/Methodology/Approach: This study proposed a conceptual framework and collected a total of 255 samples in the Mainland China to test research hypothesis and investigate the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Where consumers will decide to transact because the quality of the website has a good performance in facilitating every purchase decision-making process. In addition, it is reinforced by the findings of the model (H2c, accepted) and confirmed by research (Jiang et al, 2015;Tandon et al, 2020) that the role of e-shopping decisions as a mediator of website quality on e-repurchase intention has a positive and significant effect. Where decision ability plays an important role in intervening website quality to create repurchase intention.…”
Section: Discussionmentioning
confidence: 62%
“…Where consumers will decide to transact because the quality of the website has a good performance in facilitating every purchase decision-making process. In addition, it is reinforced by the findings of the model (H2c, accepted) and confirmed by research (Jiang et al, 2015;Tandon et al, 2020) that the role of e-shopping decisions as a mediator of website quality on e-repurchase intention has a positive and significant effect. Where decision ability plays an important role in intervening website quality to create repurchase intention.…”
Section: Discussionmentioning
confidence: 62%
“…Perceived website performance, which is directly related to internet speed, demonstrated that slow and unresponsive websites result in customer dissatisfaction with the overall experience, emphasizing the significant role of fast internet speed in an online setting [42]. In addition, service quality positively correlates with customer satisfaction; considering that service quality as a key determinant of customer satisfaction, focusing on enhancing service quality to enhance customer satisfaction is crucial [43].…”
Section: Hypothesis 10 (H10)mentioning
confidence: 99%